Magnetic ordering in the layered oxide arsenide Sr2Cr3As2O3 - Dr Simon Clarke; Mr Xiaoyu Xu; Dr Fabio Orlandi; Dr Simon Cassidy; Mr Bradley Sheath (ISIS Facility, 2019)
This experiment will probe the evolution of magnetic ordering in Sr2Cr3As2O3, a compound containing Cr3+ moments in Cr2O square layers and Cr2+ moments in CrO2 layers. We will use temperature dependent measurements on WISH to probe the magnetic ordering on the two sublattices and whether there is any interaction between the two as well as any effects of the magnetic ordering on the crystal structure. We will compare the behaviour with that of related oxide arsenide and oxide chalcogenide compounds. This is a resubmission of RB1820061 as advised by the panel.
Keywords: STFC ISIS Neutron and Muon Data